2001
DOI: 10.1097/00006534-200105000-00044
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis and Pulmonary Embolus after Face Lift: A Study of Incidence and Prophylaxis

Abstract: Deep venous thrombosis and pulmonary embolus are known risks of surgery. However, the incidence of these conditions in face lift is unknown. In this study, the incidence of deep venous thrombosis/pulmonary embolus after face lift is studied and factors associated with thromboembolic complications are evaluated. One-third of the active members of the American Society for Aesthetic Plastic Surgery were randomly selected. Participating surgeons completed a one-page survey providing information on face-lift proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(62 citation statements)
references
References 28 publications
4
53
0
5
Order By: Relevance
“…7). This represents 0.01 percent of procedures performed, consistent with the report by Reinish et al 13 As with the study by Morello et al, the Reinish group's study was conducted through a voluntary survey. The correlation of statistics with the mandatory AAAASF quality improvement and peer review Internet-based reporting system is significant.…”
Section: Deep Vein Thrombosis or Pulmonary Embolismsupporting
confidence: 81%
See 1 more Smart Citation
“…7). This represents 0.01 percent of procedures performed, consistent with the report by Reinish et al 13 As with the study by Morello et al, the Reinish group's study was conducted through a voluntary survey. The correlation of statistics with the mandatory AAAASF quality improvement and peer review Internet-based reporting system is significant.…”
Section: Deep Vein Thrombosis or Pulmonary Embolismsupporting
confidence: 81%
“…14 Fatal pulmonary emboli occur in 0.1 to 0.8 percent of general surgery patients, 2 to 3 percent of patients undergoing elective hip replacement, and 4 to 7 percent of patients undergoing operative reduction of hip fracture. 14 In a study of patients undergoing face lift surgery, Reinisch et al 13 reported an incidence of thrombosis of 0.1 percent based on a survey of selected surgeons from the American Society of Plastic and Reconstructive Surgeons. In that study, 37 of 9493 face lift patients developed deep vein thrombosis (0.39 percent) and 15 patients developed pulmonary embolism (0.16 percent).…”
Section: Deep Vein Thrombosis or Pulmonary Embolismmentioning
confidence: 99%
“…When the micro-thrombi are brought by the blood flow to a major vein, deep vein thrombi would form and may induce death if they completely occlude the major pulmonary circulation (Grabowski, 1995;Hume et al, 1970). Another case is that deep venous thrombosis and pulmonary embolus happened in 1 of 200 cases after face-lift plastic surgery (Reinisch et al, 2001;Most et al, 2005). This may be also due to the bending and stretching in the microvessels during the operation.…”
Section: Effects Of Shear Stress/rate On Thrombosismentioning
confidence: 99%
“…This same study demonstrated that 83.7 percent of the face lift patients who developed venous thromboembolism had received general anesthesia, whereas only 16.3 percent of the venous thromboembolism cases occurred with local anesthesia and sedation. 5 Grazer and Goldwyn 6 reported a deep venous thrombosis incidence of 1.1 percent and pulmonary embolism incidence of 0.8 percent in abdominoplasty patients. Applying these percentages to the 2001 national plastic surgery statistics for abdominoplasty indicates 644 cases of deep venous thrombosis and 468 cases of pulmonary embolism for that year.…”
Section: Incidencementioning
confidence: 98%